2022
DOI: 10.21037/atm-22-4709
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ATP1B1, a key copy number driver gene in diffuse large B-cell lymphoma and potential target for drugs

Abstract: Background: Copy number variations (CNVs) participate in the development and progression of cancer by altering the expression levels of genes. However, it is unclear whether this correlation exists in diffuse large B-cell lymphoma (DLBCL).Methods: Differentially expressed genes (DEGs) were identified from the GSE25638 and GSE56315 datasets. Modules that were highly related to DLBCL prognosis were obtained by Weighted Gene Coexpression Network Analysis (WGCNA). We performed an integrated analysis between CNV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…S2 A. Previous studies have reported that CNV levels are positively correlated with the malignancy of T-cell [ 52 ] and B-cell [ 53 ] lymphomas. So InferCNVs analysis was performed across B cell subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…S2 A. Previous studies have reported that CNV levels are positively correlated with the malignancy of T-cell [ 52 ] and B-cell [ 53 ] lymphomas. So InferCNVs analysis was performed across B cell subtypes.…”
Section: Resultsmentioning
confidence: 99%